COVID-19 vaccination: public preference and intention in Vietnam - Tran, V. D.; Huynh, T. M. D.; Pham, D. T.; Le, M. H.; Dorofeeva, V. V.; Dewey, R. S. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Backgrounds. Understanding public opinion in relation to vaccination is critical, as there are several COVID-19 vaccines approved for use in Vietnam. This study aimed to assess public COVID-19 vaccine preferences and intention in Can Tho, Vietnam. Methods. An analytical cross-sectional study was performed between September 20 and October 20, 2021. in people aged 18 and over living in Can Tho, Vietnam, A questionnaire captured demographic information, vaccination intention, preference for vaccine selection, and barriers and motivations related to COVID-19 vaccination. Predictors for vaccination willingness among unvaccinated people were determined using multivariable logistic regression. Results. Out of the proposed vaccines that have been approved by the Vietnam Ministry of Health, AstraZeneca (31.4%), Pfizer (23.5%), and Moderna (14.7%) were the most preferred by participants. Out of 1,470 respondents, 35.8% have received at least one vaccine dose, and of these, 76.9% intended to continue to receive vaccinations. Among the unvaccinated, 74.8% reported that they would be willing to complete the vaccination. Most participants stated that they would receive a COVID-19 vaccine if provided with adequate information on effectiveness and safety (92.7%). The possibility of side effects after vaccination (75.4%) was the most important barrier to vaccination. Education, health status, and prior flu-vaccination were associated with the intention to receive a COVID-19 vaccination among those who had not previously received one. Conclusions. Many unvaccinated adults were willing to receive a COVID-19 vaccination, with AstraZeneca being the preferred choice. These findings could help in the planning of vaccination campaigns to increase vaccination uptake in Vietnam.